ICARDA’s Research on Rangeland Governance and Pastoral Development: Institutional Arrangements for Economic Development - Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
ICARDA’s Research on Rangeland Governance and Pastoral Development: Institutional Arrangements for Economic Development